PENGARUH TAX MINIMIZATION, EXCHANGE RATE DAN TUNNELING INCENTIVE TERHADAP KEPUTUSAN TRANSFER PRICING - Wulandari Cahyani Putri; Lindawati Lindawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to find out and test empirically the effect of tax minimization, exchange rates and tunneling incentives on transfer tricing decisions in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2020. The type of research used is associative quantitative which uses secondary data in the form of financial reports that have been published by the company on the Indonesia Stock Exchange. The population of this study were 138 companies and the selected sample was 11 companies using purposive sampling method, with 61 data analyzed. The data analysis technique for testing this hypothesis was carried out using the Eviews 9 application. The results of this study show that simultaneously tax minimization, exchange rate and tunneling incentives have a significant effect on transfer pricing. Partially, tax minimization has no effect on transfer pricing, the exchange rate has a significant positive effect on transfer pricing. Tunneling incentive has a significant positive effect on transfer pricing.